2017
DOI: 10.1182/blood-2016-11-748822
|View full text |Cite
|
Sign up to set email alerts
|

Correcting the hemophilic imbalance

Abstract: In this issue of Blood, Polderdijk et al design and evaluate a therapeutic inhibitor of activated protein C.1 They have produced a recombinant variant of a1- antitrypsin (a1AT) incorporating 3 residue changes within the P2-P19 sequence of its reactive loop. This variant (termed KRK a1AT) exhibits high specificity and inhibitory efficiency toward activated protein C. It is able to restore thrombin generation in normal and in hemophilia plasmas, when these are supplemented with soluble thrombomodulin. It is able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…On the other hand, TP53 mutations in Shwachman-Diamond are controversial in that the mutations do not augur for transformation (Xia et al, 2018 ). Furthermore, the prevalence of mutations in TP53 and in other genes such RUNX1 in Fanconi anemia or dyskeratosis congenita appears to be much less than that of CSF3R in SCN (Chao et al, 2017 ; Lane, 2017 ; Kirschner et al, 2018 ). Despite this, modified Moran model might be applicable to other bone marrow failure syndromes that are associated with leukemia transformation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, TP53 mutations in Shwachman-Diamond are controversial in that the mutations do not augur for transformation (Xia et al, 2018 ). Furthermore, the prevalence of mutations in TP53 and in other genes such RUNX1 in Fanconi anemia or dyskeratosis congenita appears to be much less than that of CSF3R in SCN (Chao et al, 2017 ; Lane, 2017 ; Kirschner et al, 2018 ). Despite this, modified Moran model might be applicable to other bone marrow failure syndromes that are associated with leukemia transformation.…”
Section: Discussionmentioning
confidence: 99%
“…1). [46][47][48] APC is activated from its precursor, protein C, by thrombin bound to thrombomodulin on the endothelial cell surface. 46 Once formed, APC exerts its anticoagulant activity by proteolytically inactivating FVIIIa and activated factor V (FVa).…”
Section: Anti-activated Protein Cmentioning
confidence: 99%
“…However, several lines of evidence have demonstrated that the hemostatic balance may also be restored by inhibiting/reducing the natural anticoagulants even without replacing the missing procoagulant. 26 Clinical evidence has been provided by the observation that coinheritance of thrombophilic risk factors can moderate the clinical phenotype of severe hemophilia A. 27,28 Thrombin generation is increased in the plasma of individuals with coinheritance of hemophilia and some thrombophilias (eg, protein C deficiency).…”
Section: Agents That Alter the Hemostatic Balancementioning
confidence: 99%